Proteksi Hukum Dalam Peretasan (Pencurian) Data Pribadi Nasional - Dermawan, Haris; Lubis, Junaidi; Lubis, Muhammad Koginta (Universitas Muara Bungo, 2025)
The incident of data theft or cyber attack (ransomware) some time ago taught us how important legal protection is as early as possible so that the same incident does not happen again in the future. That the law in this case must be able to protect as early as possible so that the same incident does not happen again and even if it does happen again, the law must be able to fully protect the data so that legal certainty is created in the protection of personal data nationally. What is protected by law is to protect important information and protect data from loss, damage to theft, how important the law is in protecting this kind of thing. The purpose of this study is to find out how important the law is in providing data protection from all forms of damage, loss to theft which can clearly harm many people and have an impact on the emergence of legal uncertainty in providing personal data nationally. The government in this case should create a clear and firm legal umbrella to provide security to every user of personal data so that hacked data can be protected by law and resolved in the best possible way, so that there is legal certainty for all users of personal data. The purpose of this study is to find out how the law provides national personal data protection. The method used in this case is by looking at various kinds of legal rules related to the protection of personal data normatively so that there is legal certainty from the side of the legal rules that have been determined by the provisions of the laws and regulations in force in Indonesia. The results of the study indicate that the legal rules are still weak so that the law has not been able to provide protection as early as possible for legal certainty in protecting all personal data nationally.